2016
DOI: 10.1007/s11999-015-4216-y
|View full text |Cite
|
Sign up to set email alerts
|

The Mark Coventry Award: Custom Cutting Guides Do Not Improve Total Knee Arthroplasty Clinical Outcomes at 2 Years Followup

Abstract: Background Custom cutting guides (CCGs; sometimes called patient-specific instrumentation [PSI]) in total knee arthroplasty (TKA) use preoperative three-dimensional imaging to fabricate cutting blocks specific to a patient's native anatomy. Questions/purposes The purposes of this study were to determine if CCGs (1) improve clinical outcomes as measured by UCLA activity, SF-12, and Oxford knee scores; and (2) coronal mechanical alignment versus standard alignment guides. Methods This was a retrospective cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…In their study of VISIONAIRE TKAs, Pfitzner et al reported no difference in Knee Society pain and function scores and Western Ontario and McMaster Universities Arthritis Index (WOMAC) for the PSI and conventional TKA groups at 3 months postoperatively [34]. Similarly, Nam et al report no benefit in range of motion or patient-reported outcomes for PSI compared to conventional TKAs, as well as no difference in the number of outliers (±3°from neutral) for long-leg alignment, at a mean follow-up of greater than 2 years [29]. Other studies have noted similar findings [43,44].…”
Section: Discussionmentioning
confidence: 98%
“…In their study of VISIONAIRE TKAs, Pfitzner et al reported no difference in Knee Society pain and function scores and Western Ontario and McMaster Universities Arthritis Index (WOMAC) for the PSI and conventional TKA groups at 3 months postoperatively [34]. Similarly, Nam et al report no benefit in range of motion or patient-reported outcomes for PSI compared to conventional TKAs, as well as no difference in the number of outliers (±3°from neutral) for long-leg alignment, at a mean follow-up of greater than 2 years [29]. Other studies have noted similar findings [43,44].…”
Section: Discussionmentioning
confidence: 98%
“…As a result of the link between implant alignment outliers and early implant failure, efforts have been made to optimize alignment with the use of robotic navigation and patient-specific instrumentation [19][20][21][22][23][24][25][26][27][28][29][30][31][32] . However, little work has been conducted to identify the primary surgeon-specific factors that drive these outliers in order to understand the optimal patient populations in which to utilize this expensive technology.…”
mentioning
confidence: 99%
“…Additionally, manual instrumentation was used for the neutral MA group compared with this study that used computer navigation. Although previous studies report no difference in patient-reported outcomes between TKAs performed with PSI versus manual instrumentation [35,43], a meta-analysis of Level I studies did report a small functional advantage (mean 7-point increase in KSS score) for mechanically aligned TKAs performed with computer navigation versus manual instruments [38].…”
Section: Discussionmentioning
confidence: 94%